Two Western Australian Primary Schools’ Responses to the Australian Curriculum, Assessment and Reporting Authority Guidelines on internationalisation in schools - Oakes, Ivan Alvin James (Curtin University, 2017)
This study explores the extent to which two Western Australian primary schools are embracing internationalisation in response to the expectations set by the Australian Curriculum Assessment, and Reporting Authority (ACARA). Findings indicate that to some extent the two schools are internationalising their learning and teaching, curriculum and school activities but the focus is limited due to many intervening factors. The thesis makes recommendations for the improvement of internationalisation strategies in schools.